Removal of methylene blue from aqueous solution by ionic liquid - Kermanioryani, M. (Trans Tech Publications Ltd, 2014)
The frequent usage of cationic dyes is in the textile and leather industries. However, they are not only utilized during the dying process, but also they are recovered at the end of the process. Hence, the removal of dye from huge quantity of wastewater is necessary. In this paper methylene blue as a cationic dye have been extracted successfully into an ionic liquid namely 1-hexyl-3- methyl-imidazolium bis (trifluoromethylsulfonyl) imide, abbreviated as HMIMTF2N. To investigate the feasibility of using (IL) to dye removal from aqueous solutions batch experiments were performed under different process conditions like initial dye concentration, pH and temperature. Also adsorption data were analyzed using isotherms models and was found to conform to the principle of Lagmuir model with good correlation coefficients (R2 = 0.9896). Â© 2014 Trans Tech Publications, Switzerland.